Nucleotide polymorphism of aquaporin from kelampayan (neolamarckia cadamba) - Ho, Zhung Khiong (University Malaysia Sarawak, UNIMAS., 2013)
Neolamarckia cadamba (Roxb.) Bosser is locally known as Kelampayan in Malaysia. Aquaporin facilitates rapid transmembrane flow of water throughout the plant to enable better survival of plants as water is essential in every living organism. Due to various environmental factors such as soil salinity, nutrient deficiency, day and night cycles, or anaerobiosis which might affect the growth of Kelampayan trees, it is crucial to study the aquaporin gene in Kelampayan. Roots can regulate their hydraulic conductivity in response to environmental changes well.Partial genomic sequence of aquaporin was amplified by the specific primer and subsequently examined on 1.5% agarose gel. The amplified PCR products were purified from the gel. Then, the purified PCR products were sent for sequencing and data obtained was analyzed. From the consensus sequence alignment, 2 single nucleotide polymorphisms (SNPs) were identified in the aquaporin gene. All the SNPs were found in the coding region. SNPs can be used as a marker in genetic association studies in order to determine the genotype that contributes to desired aquaporin profiles. These SNP markers will be important in linkage study to identify Quantitative Trait Nucleotide (QTN), which then leads to gene-assisted selection in the tree breeding programme.